Contribution of vertical strength and power to sprint performance in young male athletes - Meylan, C. M. P.; Cronin, J.; Oliver, J. L.; Hopkins, W. G.; Pinder, S. (International Journal of Sports Medicine, 2014)
The purpose of this study was to assess the possible contribution of 1RM leg-press strength and jump peak power to 20-m sprint time in young athletes in three maturity groups based on age relative to predicted age of peak height velocity (PHV): Pre (- 2.5 to -1.0 years; n=25), Mid (- 1.0 to 0.5 years; n=26) and Post (0.5 to 2.0 years; n=15). Allometric scaling factors, representing percent difference in 20-m time per percent difference in strength and peak power, were derived by linear regression and were similar in the three maturity groups (-0.16%/% and -0.20%/% for strength and peak power, respectively). The moderate increase in sprint performance Pre to Mid PHV (5.7%) reduced to small (1.9%) and trivial but unclear (0.9%) magnitudes after adjustment for 1RM and peak power, while the moderate increase Mid to Post PHV (4.6%) were still moderate (3.4 and 3.0%) after adjustment. Thus percent differences in strength or power explained most of the maturity-related improvements in sprint performance before PHV age but only some improvements after PHV age. Factors in addition to strength and power should be identified and monitored for development of speed in athletes during puberty.